An Analysis of the Bank Employees Domains of Occupational Stress with Reference to Kottayam District, Kerala - Issac, Renji; Krishnaveni, V (International Journal of Engineering and Technology, 2018)
Occupational stress is a common phenomenon that is pervasive in every industry. The domains of stress, especially in the banking sector, consist of the demand of inter role performance, role stagnation, role expectation, conflict of role, role erosion, role overload, role isolation, personal inadequacy, role ambiguity, role distance and resource inadequacy. The work stress in the banking industry occurs because of the effects on oneâ€™s understanding of oneâ€™s working atmosphere, strengths, opportunities, potential, threats and limitations, while performing a designated role. A gender based study was conducted among 50 bank employees in Kottayam district, Kerala. The gender was taken as an independent variable and stress id taken a dependent variable for the study. The study analysed turbulence, heavy workload and long working hours that have become the norm in the industry. Different elements of stress led to a decline in personal health, relations with colleagues and dissatisfaction with life itself, which affected efficiency and productivity. The study revealed that both the male and female respondents were affected with overload, responsibility, lack of participation, unreasonable work pressure, poor peer relations, intrinsic impoverishment, low status, strenuous working conditions and poor results. The level of significance(p<.05) and the available scores were more that the significance value, except the values of role ambiguity and role conflict.Â